Mean girl feminism how white feminists gaslight, gatekeep, and girlboss - Nguyen, Kim Hong 1981- (University of Illinois Press, 2024)
"Mean girl feminism encourages girls and women to be sassy, sarcastic, and ironic as feminist performance. Yet it coopts its affect, form, and content, from racialized oppression and protest while directing meanness toward people in marginalized groups. Kim Hong Nguyen examines four types of white mean girl feminism prominent in North American popular culture: the bitch, the mean girl, the power couple, and the global mother. White feminists mime the anger, disempowerment, and resistance felt by people of color and other marginalized groups. Their performance allows them to pursue and claim a special place within established power structures, present as intellectually superior, advance their girl squads and their partners as part of a politics of solidarity and community, and position themselves as better, more enlightened masters than men. But, as Nguyen argues, the racialized meanness found across pop culture opens possibilities for building an intersectional feminist politics that rejects performative civility in favor of turning anger into liberation"--
Keywords: Rassismus; Popkultur; Feminismus; Weiße Frau; Nordamerika; White feminism / North America; Feminism and racism / North America; Féminisme blanc / Amérique du Nord; Feminism and racism; White feminism; North America